Translation and Validation of the Thai Forgotten Joint Score for Knee Arthroplasty Patients - Taweekitikul, MD, Pariwat; Ngarmukos, MD, Srihatach; Tanavalee, MD, Aree (Journal of Southeast Asian Orthopaedics, 2022)
Introduction: Several patient-reported outcome measurements (PROMs) are used to evaluate the outcomes after knee arthroplasty. Joint awareness in everyday life, which is a new aspect to evaluate the outcome and the ability to forget the artificial joint, is claimed as the ultimate goal resulting in maximum patient satisfaction. The purpose of this study is to translate and validate a Thai version of the Forgotten Joint Score (TH-FJS). Methods: We performed the Thai translation procedure based on an internationally accepted standard. Between November 2017 and June 2018, we evaluated the TH-FJS for validity and reliability. In the validity study, the patient following knee arthroplasty completed the TH-FJS questionnaire, Oxford Knee Score (OKS), and Western Ontario & McMaster Universities Osteoarthritis Index (WOMAC). The test-retest evaluation was performed in the reliability study with a 2-week interval. A ceiling effect was defined as participants reaching a score within 15% of the maximum score. Results: There were 85 patients (average age, 71.0 years) included in this study. The test-retest reliability of the TH-FJS was high with an intraclass correlation coefficient (ICC) = 0.95 (95% CI 0.9, 0.97). We found a high level of internal consistency with a Cronbach’s α of 0.92. The ceiling effect for the TH-FJS was 28%, as compared to 49% for OKS, and 58% for WOMAC. Conclusion: The Thai language version of the FJS had high level of internal consistency and was proved to be a reliable tool for evaluating knee arthroplasty patients in Thailand. The low ceiling effect characteristic of the score can help the surgeon to detect small difference in the good and excellent outcomes after knee arthroplasty.